Stereotactic radiosurgery for cerebral cavernous malformations: A systematic review. (19th November 2019) - Poorthuis, Michiel H.F.; Rinkel, Leon A.; Lammy, Simon; Al-Shahi Salman, Rustam
Abstract : Objective: The efficacy of stereotactic radiosurgery (SRS) for the treatment of cerebral cavernous malformations (CCMs) is uncertain, so we set out to quantify clinical outcomes after SRS for CCM and compare them to microsurgical excision or conservative management. Methods: We searched Ovid Medline and Ovid EMBASE from inception until June 1, 2018, for peer-reviewed publications describing clinical outcomes after SRS for ≥10 people with CCM in cohorts with or without a comparison group treated with neurosurgical excision or conservative management. Two reviewers independently extracted data from the included studies to quantify cohort characteristics and the incidence of the primary outcome (death attributable to CCM or its treatment) and secondary outcomes (incident nonfatal symptomatic intracerebral hemorrhage [ICH] and incident nonhemorrhagic persistent focal neurologic deficit [FND]). We assessed whether comparative studies showed a dramatic association (meaning the conventionally calculated probability comparing 2 differently managed patient groups from the same population was <0.01 with a rate ratio greater than 10). Results: We included 30 cohort studies involving a total of 1, 576 patients undergoing SRS for CCM. Four nonrandomized studies compared SRS to other treatment strategies, but did not demonstrate dramatic associations. During a median follow-up of 48 (interquartile range 35–62) months after SRS, the annual incidences (95% confidence interval) of outcomes were death 0.18% (0.10–0.31), ICH 2.40% (2.05–2.80), FND 0.71% (0.53–0.96), and the composite of death, ICH, or FND 3.63% (3.17–4.16). Outcomes did not differ by CCM location or type of SRS. Conclusion: After SRS for CCM, the annual incidences of death, ICH, and FND are <5% and seem comparable to outcomes without SRS. A randomized trial of SRS for CCM is needed.